Water table contribution to alfalfa water use different environments of the Argentine Pampas - Dardanelli, J.=700 1 Collino, D.J.
(En)
ilus., 22 ref.
Keywords: ALFALFA; CAPA FREATICA; ABSORCION DE AGUA; RELACIONES PLANTA AGUA; EFICIENCIA EN EL USO DEL AGUA